2023
DOI: 10.1186/s40463-022-00612-7
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in publication rates at Canadian Society of Otolaryngology–Head and Neck Surgery annual meetings: An 11-year analysis

Abstract: Background Evaluating gender differences in publication rates after conference presentations is an avenue to assess women’s contributions to academic medicine. The objective of this study was to assess gender differences in publication rates, time to publication, and subspeciality of publication of abstracts presented at Canadian otolaryngology conferences over an 11-year period. Methods Cross-sectional data was obtained from online conference sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…9 However, women in otolaryngology seem to have more difficulty in publishing their research compared to men, as shown in a recent Canadian study. 27 Female representation is expected to increase through the years, as more women seem to enter medical school and more barriers impairing their advancement are lifted. Indeed, a greater percentage of women seem to follow surgical residency than in the past.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, women in otolaryngology seem to have more difficulty in publishing their research compared to men, as shown in a recent Canadian study. 27 Female representation is expected to increase through the years, as more women seem to enter medical school and more barriers impairing their advancement are lifted. Indeed, a greater percentage of women seem to follow surgical residency than in the past.…”
Section: Discussionmentioning
confidence: 99%